Manajemen Risiko Pembiayaan KPA Trans Icon di Bank Mega Syariah dalam Perspektif Maqashid Al Shariah - Rahayuningsih, Eka (ITB AAS INDONESIA Surakarta, 2023)
Sharia banking products to meet the demands of modern society are the development of hybrid contracts. This is because the single contract form is no longer able to respond to contemporary financial transactions. Surabaya, as the second metropolitan city in Indonesia, will of course bring it residents towards a more modern and classier life. This modern and classy residence is called Trans Icon. This research uses qualitative research. The aim of this research is to find out how Trans Icon KPA Financing Risk Management is at Bank mega Syariah form a maqashid al shariah perspective. Sharia principles in sharia financial institutions are based on the values of justice, balance, benefit, and universalism. The main principles of sharia financial institutions in carrying out their business are freedom from maysir, gharar, haram things, usury, and from falsehood. Risk management of KPA Trans Icon financing in the face of bad financing or defaulting customers, namely by efforts ti save financing and resolve. The concepts used in financing KPA Trans Icon at Bank Mega Syariah Surabaya is the Musyarakah Mutanaqishah concept, the procedure for fimancing is very easy and simple, consisting of six stages, namely character, capacity, collateral, capital, financing approval, binding and disbursement.